Prepreg material, method for preparing the prepreg material, and fiber-reinforced composite material prepared from the prepreg material

By carrying out a two-step lamination process under high temperature and high pressure and low temperature medium pressure conditions, the wetting performance and adhesion of aramid fiber substrate to resin is improved, the void problem in fiber reinforced composite materials is solved, the strength of the material is improved and the moisture absorption rate is reduced.

CN114829468BActive Publication Date: 2025-04-01KOLON INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080087382.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-02
Filing Date
2020-12-10
Publication Date
2025-04-01
Estimated Expiration
2040-12-10

AI Technical Summary

Technical Problem

Among the existing fiber-reinforced composite materials, the poor wetting performance of aramid fibers and poor compatibility with matrix resins lead to voids that are prone to appear during the curing process, affecting the strength and moisture absorption of the material.

Method used

By performing the first lamination step under high temperature and high pressure conditions, the resin film is laminated on the aramid fiber substrate, and the second lamination step is carried out at low temperature and medium pressure conditions, the wetting performance and adhesion of the aramid fiber substrate to the resin is improved, thereby preparing a high-quality prepreg material.

Benefits of technology

This method improves the strength of the fiber-reinforced composite and reduces moisture absorption, ensuring high-quality molding of the material without the need for expensive autoclave equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003698294460000091
    Figure BDA0003698294460000091
Patent Text Reader

Abstract

The present disclosure relates to a prepreg material, a method for preparing the prepreg material, and a fiber-reinforced composite material prepared from the prepreg material. The method for preparing the prepreg material may include an aramid fiber substrate having improved wetting properties for a resin, capable of increasing a thickness reduction rate during the prepreg material molding process, having a suitable resin content, and capable of providing a prepreg material suitable for molding by a non-autoclave process. In addition, the prepreg material may provide a fiber-reinforced composite material that exhibits a thin thickness and a high resin content even by a non-autoclave process, and exhibits high strength and a low moisture absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a prepreg material, a method for preparing the prepreg material, and a fiber-reinforced composite material prepared from the prepreg material. Background Art

[0002] Fiber-reinforced composite materials prepared by impregnating a matrix resin in a fiber material for reinforcement and then curing have been widely used in various fields such as electronic parts, automobile parts, and the like.

[0003] Glass fiber or carbon fiber has been mainly used as a fiber material for reinforcement. However, glass fiber has a high specific gravity, so it is difficult to reduce the weight, and glass fiber is also harmful to the human body, while carbon fiber has a high specific stiffness, so it is poor in machinability and impact resistance.

[0004] As an alternative to solve these problems, a technology using aramid fibers has been introduced. However, aramid fibers have poor wetting properties compared to glass fibers or carbon fibers and poor compatibility with matrix resins, thus causing additional problems such as the generation of voids after curing into fiber-reinforced composite materials. Summary of the invention

[0005] Technical issues

[0006] In the present disclosure, a method for preparing a prepreg material is provided.

[0007] Also provided are a prepreg material prepared by the method for preparing the prepreg material and a fiber-reinforced composite material prepared by the prepreg material.

[0008] Technical Solution

[0009] Hereinafter, a method for preparing a prepreg material according to a specific embodiment of the present disclosure, a prepreg material prepared by the preparation method, and a fiber-reinforced composite material prepared by the prepreg material will be described.

[0010] According to one embodiment, there is provided a method for preparing a prepreg material, comprising:

[0011] a first lamination step of laminating a resin film on an aramid fiber substrate and applying pressure; and a second lamination step of applying pressure to the laminate obtained by the first lamination step,

[0012] Wherein, a lower pressure is applied at a lower temperature in the second lamination step than in the first lamination step.

[0013] As a result of research on improving the wetting properties of aramid fibers of fiber-reinforced composite materials to resin, the inventors have confirmed that when a prepreg material (which is an intermediate material for preparing a fiber-reinforced composite material) is prepared by a first lamination step carried out under high temperature and high pressure conditions and a second lamination step carried out under low temperature and medium pressure conditions, a high-quality fiber-reinforced composite material can be obtained by improving the wetting properties of the aramid fiber substrate to the resin during the prepreg molding process.

[0014] Specifically, the inventors have developed a method for preparing a prepreg material with a suitable resin content, taking into account the elastic recovery properties of the aramid fiber substrate, the viscosity properties and curing properties of the resin film under the conditions of preparing and molding the prepreg material, while improving the thickness reduction rate during the molding process of the prepreg material.

[0015] The first lamination step of the preparation method according to one embodiment can maximize the permeability of the resin so that the resin film can deeply penetrate into the aramid fiber substrate, and the first lamination step can be performed at high temperature and high pressure so that a suitable content of the resin can be impregnated into the aramid fiber substrate.

[0016] Specifically, the first lamination step may be performed at a temperature of 80 to 90° C., 82 to 88° C., or 84 to 86° C. Within the above temperature range, the permeability of the resin may be maximized while the resin film is not hardened, and an unimpregnated portion may not appear inside the aramid fiber substrate, thereby preventing problems such as strength reduction and high moisture absorption rate caused by an unimpregnated area or a dry area that appears in a subsequent molding process from occurring.

[0017] In addition, the first lamination step can be performed at a pressure of 2.6 bar to 5 bar, 2.8 bar to 4.5 bar, or 3 bar to 4 bar. Like this, when high pressure is applied to the resin film laminated on both sides of the aramid fiber substrate at high temperature, the viscosity of the resin may be reduced, and the resin can easily penetrate between the fibers of the aramid fiber substrate, so that the unimpregnated part may not appear inside the aramid fiber substrate, thereby preventing the occurrence of problems such as reduced strength and high moisture absorption rate. In addition, when the pressure is removed after the high pressure is applied to the aramid fiber substrate, a relatively large void may be formed inside the prepreg material due to the elastic recovery of the aramid fiber substrate. Due to the large void, the prepreg material can have an increased thickness reduction rate during the molding process.

[0018] The second lamination step of the production method according to one embodiment described above may be performed at low temperature and medium pressure to improve resin adhesion, impregnation properties, etc. near the surface of the aramid fiber substrate and provide an appropriate level of resin content.

[0019] Specifically, the second lamination step may be performed at a temperature of 70° C. to 79° C., 70° C. to 75° C., or 70° C. to 73° C. In addition, the second lamination step may be performed at a pressure of 1.5 to 2.5 bar, 1.7 to 2.3 bar, or 1.8 to 2.2 bar. As such, when a medium pressure is applied to the laminate at a low temperature, the elastic recovery degree of the aramid fiber substrate and the viscosity of the resin may be controlled at appropriate levels to improve adhesion to the resin near the surface of the aramid fiber substrate and impregnation of the resin, and improve surface quality while increasing the resin content in the prepreg material.

[0020] The preparation method according to one embodiment can be performed in a continuous process. Specifically, the aramid fiber substrate and the resin film can be continuously supplied so that the resin film is laminated on both sides of the aramid fiber substrate. More specifically, the aramid fiber substrate and the resin film can be continuously supplied by a roller and can be laminated by a pressure roller having a heated surface. As an example, the first lamination step and the second lamination step can be performed by at least two rollers, wherein at least one roller can pressurize the resin film laminated on both sides of the aramid fiber substrate under high pressure (for example, 2.6 bar to 5 bar, 2.8 bar to 4.5 bar or 3 bar to 4 bar) when the surface temperature is heated to a high temperature (for example, 80°C to 90°C, 82°C to 88°C or 84°C to 86°C), and at least another roller can pressurize the laminate under medium pressure (for example, 1.5 bar to 2.5 bar, 1.7 bar to 2.3 bar or 1.8 bar to 2.2 bar) when the surface temperature is heated to a low temperature (for example, 70°C to 79°C, 70°C to 75°C or 70°C to 73°C).

[0021] At this time, the resin film may be sufficiently impregnated up to the center of the aramid fiber substrate by adjusting the feed rate in the first lamination step to 0.1 to 1.5 m / min, 0.1 to 1.0 m / min, or 0.1 to 0.8 m / min.

[0022] In the second lamination step, the feed speed of the laminate may be adjusted to be the same as that in the first lamination step, in that the second lamination step may be performed in a continuous process with the first lamination step.

[0023] The aramid fiber substrate that can be used in the preparation method according to one embodiment can be a fabric woven with aramid fibers. In this case, a prepreg material having excellent mechanical properties can be prepared by maximizing the impregnation performance of the resin by using fibers of 1500 to 3500 deniers as aramid fibers.

[0024] In the production method according to one embodiment, by using a resin film cured at a temperature of about 90° C. to 130° C., the resin film can be prevented from being cured in the first lamination step and the second lamination step.

[0025] In addition, by using a resin film having an absolute viscosity of about 5 Pa·s to 10 Pa·s at about 70° C., the impregnation performance of the resin film into the aramid fiber substrate can be improved.

[0026] The absolute viscosity may be a viscosity value measured at about 70° C. by using a rotational rheometer after preparing a sample having a diameter of about 300 mm and a thickness of about 300 μm.

[0027] Such a resin film may include a thermoplastic resin, a thermosetting resin, or a mixture thereof.

[0028] For example, the resin film may be formed of a thermosetting resin composition. The main resin of the thermosetting resin composition may be at least one selected from epoxy resin, phenol resin, unsaturated polyester resin, cyanate resin, and the like.

[0029] The resin film may be formed of a thermosetting resin composition including an epoxy resin.

[0030] The epoxy resin included in the thermosetting resin composition may refer to a material having two or more epoxy groups in a molecule or a resin prepared by polymerization of the material. As the epoxy resin, for example, at least one selected from the following can be used: bisphenol type epoxy resins, such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin and bisphenol S type epoxy resin; brominated epoxy resins, such as tetrabromobisphenol A diglycidyl ether; epoxy resins having a biphenyl skeleton; epoxy resins having a naphthalene skeleton; epoxy resins having a dicyclopentadiene skeleton; novolac type epoxy resins, such as phenol novolac type epoxy resin and cresol novolac type epoxy resin; and glycidylamine type epoxy resins, such as diaminodiphenylmethane type epoxy resin, diaminodiphenyl sulfone type epoxy resin, aminophenol type epoxy resin, meta-xylene diamine type epoxy resin, 1,3-bis(aminomethyl)cyclohexane type epoxy resin (1,3-bisaminomethylcyclohexane type epoxy resin) and isocyanurate type epoxy resin.

[0031] In addition, the thermosetting resin composition can include a curing agent for curing epoxy resin. Compounds with reactive groups that can be cross-linked with epoxy groups can be used as curing agents. Examples of the curing agent can include dicyandiamide, diaminodiphenylmethane, diaminodiphenyl sulfone, aminobenzoic acid esters, various anhydrides, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, fatty amines, tetramethylguanidine, thiourea-amine (thiourea-amine), methylhexahydrophthalic anhydride, other carboxylic acid anhydrides, carboxylic acid hydrazide (carboxylic acid hydrazide), carboxylic acid amide (carboxylic acid amide), polythiol, boron trifluoride ethylamine complex, other Lewis acid complexes etc.

[0032] The curing agent may be used in an amount of about 3 parts by weight to 10 parts by weight based on 100 parts by weight of the epoxy resin in order to properly cure the epoxy resin without residual curing agent.

[0033] If necessary, the thermosetting resin composition may further comprise a thermoplastic resin. For example, the thermoplastic resin may be at least one selected from polyamide, polycarbonate, polyacetal, polyphenylene oxide, polyphenylene sulfide, polyarylate, polyester, polyamide-imide, polyimide, polyetherimide, polyimide having a phenyltrimethylindane structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyaramide, polyethernitrile and polybenzimidazole.

[0034] The thermoplastic resin may be added in the form of particles or fibers. When added in the form of particles, the shape may be spherical, non-spherical, porous, whisker or flake, and when added in the form of fibers, the thermoplastic resin may be added in the form of short fibers or long fibers.

[0035] In addition to the above-mentioned components, the thermosetting resin composition may further include various additives known in the art to which the present invention belongs, for example, a curing aid and the like.

[0036] Meanwhile, according to another embodiment of the present disclosure, a prepreg material prepared according to the preparation method is provided. The prepreg material prepared according to the preparation method may include an aramid fiber substrate and a resin impregnated in the aramid fiber substrate. Since the aramid fiber substrate and the resin have been described in detail above, their detailed description will be omitted.

[0037] Specifically, the prepreg material is prepared by a two-step lamination process under specific conditions and is impregnated with resin up to the center of the prepreg material, so that it can be provided with a minimized unimpregnated area. In addition, it can also have a relatively large void, thereby showing a suitable resin content, and at the same time, it shows a large thickness reduction rate during the process of being formed into a fiber-reinforced composite material.

[0038] Specifically, the prepreg material may have a high resin content of 35 wt % to 45 wt %, 37 wt % to 43 wt %, or 39 wt % to 41 wt %.

[0039] Furthermore, the prepreg material can provide a fiber-reinforced composite material through a non-autoclave process using only a vacuum pump and an oven without using an autoclave, which is an expensive pressurizing device.

[0040] Although the existing non-autoclave process has the advantage of not using expensive pressurizing equipment, the method has the disadvantage of a high defect rate due to the formation of voids by volatile components of the resin film.

[0041] However, the prepreg material prepared by the preparation method according to one embodiment can provide a high-quality fiber-reinforced composite material even through a non-autoclave process.

[0042] Meanwhile, according to another embodiment of the present disclosure, a fiber-reinforced composite material prepared from the prepreg material is provided. The fiber-reinforced composite material may include an aramid fiber substrate and a resin cured in a state of being impregnated in the aramid fiber substrate. Since the aramid fiber substrate and the resin have been described in detail above, their detailed description will be omitted.

[0043] The fiber-reinforced composite material can be prepared from one or more prepreg materials, or from a laminate of two or more prepreg materials.

[0044] The fiber-reinforced composite material is prepared from a prepreg material prepared through a two-step lamination process under the above-mentioned specific conditions to minimize the unimpregnated area or dry area, thereby exhibiting excellent strength, low moisture absorption rate, etc.

[0045] Specifically, the fiber reinforced composite material may have a flexural strength measured according to ASTM D790 of 250 MPa to 400 MPa, 270 MPa to 350 MPa, or 300 MPa to 330 MPa.

[0046] In addition, the moisture absorption rate of the fiber-reinforced composite material calculated by the following formula 1 may be 0 wt % or more and 3 wt % or less, 2 wt % or less, or 1.7 wt % or less.

[0047] [Formula 1]

[0048] Moisture absorption rate = (weight of sample after immersion - weight of sample before immersion) / weight of sample before immersion * 100

[0049] In Formula 1, the weight of the sample before immersion is the weight before immersing the sample in distilled water; the weight of the sample after immersion is the weight of the sample measured after being completely immersed in distilled water and taken out, wherein the weight is a value measured after first removing moisture from the upper and lower parts and edges of the sample with a towel and secondarily removing moisture from the upper and lower parts with a dry towel.

[0050] For details of the method of measuring the bending strength and the moisture absorption rate, refer to the contents described in the test examples described later.

[0051] The fiber-reinforced composite material may exhibit the above-mentioned excellent flexural strength and low moisture absorption rate even when molded by a non-autoclave process.

[0052] Furthermore, the fiber reinforced composite material may exhibit a high resin content of 35 to 45 wt %, 35 to 40 wt %, 36 to 38 wt %, or 37 to 38 wt %.

[0053] Beneficial Effects

[0054] The method for preparing a prepreg material according to an embodiment of the present disclosure may include an aramid fiber substrate having improved wetting properties for a resin, can improve a thickness reduction rate during the prepreg material molding process, has a suitable resin content, and can provide a prepreg material suitable for molding by a non-autoclave process. In addition, the prepreg material can provide a fiber-reinforced composite material that exhibits a thin thickness and a high resin content even by a non-autoclave process, and the fiber-reinforced composite material exhibits high strength and low moisture absorption rate. DETAILED DESCRIPTION

[0055] Hereinafter, the functions and effects of the present invention will be described in more detail through specific embodiments. However, these embodiments are only for illustrative purposes, and the present invention is not intended to be limited to these embodiments.

[0056] Example 1: Preparation of prepreg material

[0057] A plain aramid fabric was woven using aramid yarns having a denier of about 3000 as warp and weft yarns.

[0058] At the same time, the epoxy resin composition supplied as SCP-510 from EZ Composite was heated to about 80 ± 10 g / m 2 An epoxy resin film prepared by coating a coating amount of % on a release paper and then drying was used as the resin film.

[0059] While the aramid fabric is continuously supplied, the epoxy resin film is continuously supplied to contact both sides of the aramid fabric. The feeding speed of the aramid fabric and the resin film is controlled at about 0.5 m / min.

[0060] Then, a first lamination step was performed by applying a pressure of 3 bar to the resin films laminated on both sides of the aramid fabric with a pressure roller heated to 85° C. Thereafter, a prepreg was prepared by impregnating the resin films on both sides of the aramid fabric through a second lamination step in which a pressure of 2 bar was applied to the laminate obtained in the first lamination step with a pressure roller heated again to 70° C.

[0061] Comparative Example 1: Preparation of prepreg material

[0062] A prepreg material was prepared by the same method as in Example 1, except that a first lamination step of applying pressure to the resin films laminated on both sides of the aramid fabric with a pressure roller heated to 85°C; a second lamination step of applying pressure to the resin films laminated on both sides of the aramid fabric with a pressure roller heated to 70°C; and a third lamination step of applying pressure to the resin films laminated on both sides of the aramid fabric with a pressure roller heated to 100°C were performed instead of the first lamination step and the second lamination step.

[0063] Test example: Evaluation of physical properties of prepreg materials

[0064] The physical properties of the prepreg materials prepared in Examples and Comparative Examples were evaluated by the following methods, and the results are shown in Table 1.

[0065] 1) Resin content before molding

[0066] The percentage of the mass per unit resin film to the mass per unit prepreg ((mass per unit prepreg - mass per unit aramid fabric) / mass per unit prepreg * 100) was measured and defined as the resin content (unit: wt %).

[0067] 2) Thickness, thickness change rate and resin content after molding

[0068] Four prepreg materials are laminated into four layers and then fully pressed with a roller. Then, the laminate is placed on a flat mold that has been treated with an anti-sticking agent, and a release film is laminated on it. And, with and without lamination of a backing plate (steel) of the same size as the prepreg material with a thickness of 2 mm, a vent used as an air flow path inside the vacuum bag is laminated on the release film, and finally wrapped with a vacuum bag and then sealed with a sealant. Then, a fiber-reinforced composite material is prepared by maintaining it at 125°C for 30 minutes under a vacuum pressure of 28 inches Hg while curing the prepreg material.

[0069] The thickness, thickness change rate and resin content were measured for the fiber reinforced composite material prepared with the backing plate and the fiber reinforced composite material prepared without the backing plate.

[0070] The thickness is measured by measuring the thickness at eight points in a total of four corners at two points for each corner of the sample, and then obtaining its average value, and the thickness change rate is calculated from the percentage of the thickness difference before and after molding to the thickness before molding (thickness difference before and after molding / thickness before molding×100), and the resin content is measured by the above method.

[0071] 3) Bending strength

[0072] The flexural strength of the fiber reinforced composite material prepared by using a backing plate and the fiber reinforced composite material prepared without using a backing plate were measured using a universal tensile testing machine at a temperature of 23±2°C according to ASTM D790.

[0073] 4) Water absorption rate

[0074] The moisture absorption rate of the fiber reinforced composite material prepared using the backing plate and the fiber reinforced composite material prepared without using the backing plate was measured by completely immersing the sample in distilled water. Then, the moisture absorption rate was calculated by substituting the weight before immersion and the weight after immersion into the following formula 1.

[0075] [Formula 1]

[0076] Moisture absorption rate (weight %) = (weight of sample after immersion - weight of sample before immersion) / weight of sample before immersion * 100

[0077] At this time, first remove moisture from the upper and lower parts and edges of the sample with a towel (five sheets of Kimberly-Clark paper towels, dry fabric, etc.), remove moisture from the upper and lower parts twice with a dry towel to visually remove moisture completely, and then measure the weight before and after immersion.

[0078] [Table 1]

[0079]

Claims

1. A method for preparing a prepreg material, comprising: A first lamination step is to laminate the resin film onto the aramid fiber substrate and apply pressure; and a second lamination step of applying pressure to the laminate obtained by the first lamination step, wherein a lower pressure is applied at a lower temperature in the second lamination step than in the first lamination step, The first lamination step is performed at a temperature of 80°C to 90°C, and the first lamination step is to laminate the resin film on the aramid fiber substrate and apply a pressure of 2.6 bar to 5 bar. wherein the second lamination step is performed at a temperature of 70° C. to 79° C., the second lamination step is performed by applying a pressure of 1.5 bar to 2.5 bar to the laminate obtained by the first lamination step, and The first lamination step and the second lamination step are performed by at least two rollers, at least one roller presses the resin films laminated on both sides of the aramid fiber substrate, and at least another roller directly presses the laminate.

2. The method for preparing a prepreg material according to claim 1, wherein: The first laminating step is to continuously supply the aramid fiber substrate and the resin film at a feed rate of 0.1 m / min to 1.5 m / min so that the resin film is laminated on both sides of the aramid fiber substrate.

3. The method for preparing a prepreg material according to claim 1, wherein: The aramid fiber substrate is woven from aramid fibers with a denier of 1500 to 3500.

4. The method for preparing a prepreg material according to claim 1, wherein: The resin film is cured at 90°C to 130°C.

5. The method for preparing a prepreg material according to claim 1, wherein: The absolute viscosity of the resin film at 70° C. is 5 Pa·s to 10 Pa·s.

6. The method for preparing a prepreg material according to claim 1, wherein: The resin film is formed of a thermosetting resin composition including an epoxy resin and a curing agent.

7. The method for preparing a prepreg material according to claim 6, wherein: The epoxy resin includes at least one selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, bisphenol S type epoxy resin, tetrabromobisphenol A diglycidyl ether, an epoxy resin with a biphenyl skeleton, an epoxy resin with a naphthalene skeleton, an epoxy resin with a dicyclopentadiene skeleton, a phenol novolac type epoxy resin, a cresol novolac type epoxy resin, a diaminodiphenylmethane type epoxy resin, a diaminodiphenyl sulfone type epoxy resin, an aminophenol type epoxy resin, a meta-xylene diamine type epoxy resin, a 1,3-bis(aminomethyl)cyclohexane type epoxy resin and an isocyanurate type epoxy resin.

8. A prepreg material prepared by the method for preparing a prepreg material according to claim 1. 9 . The prepreg material according to claim 8 , wherein the resin content of the prepreg material is 35 wt % to 45 wt %.

10. A fiber-reinforced composite material made of the prepreg material according to claim 8, comprising an aramid fiber substrate and a resin cured in a state of being impregnated in the aramid fiber substrate, wherein: The flexural strength measured according to ASTM D790 is 250 MPa to 400 MPa.

11. The fiber-reinforced composite material according to claim 10, wherein: The moisture absorption rate calculated by the following formula 1 is 0 to 3 weight %: [Formula 1] Moisture absorption rate = (weight of sample after immersion - weight of sample before immersion) / weight of sample before immersion * 100 In Formula 1, the weight of the sample before immersion is the weight before immersing the sample in distilled water; the weight of the sample after immersion is the weight of the sample measured after being completely immersed in distilled water and taken out, wherein the weight is a value measured after first removing water from the upper and lower parts and edges of the sample with a towel and secondarily removing water from the upper and lower parts with a dry towel.

Citation Information

Patent Citations

  • Aramid fiber enhanced cyanate ester composite material

    CN109486185A

  • Prepreg and method for manufacturing same

    EP2692783A1

  • Method for opening fiber bundle, opened yarn sheet and method for producing fiber-reinforced sheet

    JP2010270420A

  • Prepreg, and method for producing prepreg

    JP2013142123A